Lower rate limit in cardiac resynchronization therapy defibrillators. (3rd October 2022) - Barradas, M; Duarte, F; Coutinho Dos Santos, I; Resendes De Oliveira, L; Serena, C; Xavier Fontes, A; Viveiros Monteiro, A; Machado, C; Dourado, R; Santos, E; Pelicano, N; Pacheco, M; et al.
Abstract: Background: There is few data about programmed lower rate limit (LRL) in real world heart failure (HF) patients with cardiac resynchronization therapy–defibrillators (CRT-Ds) and its influence in clinical outcomes. Heart rate score (HRS) is the percentage of all atrial-paced and sensed events in the single tallest 10 beats/min device histogram bin and may indicate impaired heart rate variability. Purpose: We hypothesized that higher LRL programming is associated with worse clinical outcomes as arrhythmic events and HF decompensations in chronic HF patients with CRT-Ds. Methods: LRL was evaluated and HRS was calculated from remote monitoring in 126 HF patients with CRT-D. Primary outcome was defined as HF hospitalizations and related admissions to the emergency department and secondary outcome as number of device therapies, sustained ventricular tachycardia (VT) and ventricular fibrillation (VF). Results: Mean age was 69, 03±10, 39 years, 81 (64, 3%) were males and mean follow-up was 53, 72±46, 13 months. Mean left ventricular ejection fraction was 30, 31±8, 33% and 29 (23, 0%) were in NYHA III–IV. HF aetiology was idiopathic in 39 (43, 3%), ischemic in 32 (25, 4%) and alcoholic cardiomyopathy in 8 (6, 3%). Thirty-seven (29, 4%) patients had atrial fibrillation and 33 (26, 2%) coronary disease. LRL ranged from to 40 to 80 bpm and mean LRL was 52, 64±9, 64 and mean HRS 49, 60±23, 17%. Programmed LRL was higher in women (p=0, 014), patients with atrial fibrillation (AF) (p=0, 012) and coronary disease (p=0, 015). Higher LRL correlated with HF hospitalizations and related admissions to the emergency department (ED) (r=0, 541, p=0, 001), VT or VF episodes (r=0, 337, p=0, 005) and CRT-D number of therapies (r=0, 342, p=0, 004) and higher HRS (r=0, 547, p<0, 05). Conclusion: Higher LRL programming was associated with higher HRS, HF decompensations with hospitalization or admission to the emergency department, VT or VF episodes and CRT-D therapies in a real world population. More studies are required but lower LRL may be preferred in HF patients. Funding Acknowledgement: Type of funding sources: None.